2014
DOI: 10.1186/1471-2466-14-65
|View full text |Cite
|
Sign up to set email alerts
|

Comparative chest computed tomography findings of non-tuberculous mycobacterial lung diseases and pulmonary tuberculosis in patients with acid fast bacilli smear-positive sputum

Abstract: BackgroundEarly diagnosis and treatment of nontuberculous mycobacterial lung diseases (NTM-LD) and pulmonary tuberculosis (PTB) are important clinical issues. The present study aimed to compare and identify the chest CT characteristics that help to distinguish NTM lung disease from PTB in patients with acid-fast bacilli (AFB) smear-positive sputum.MethodsFrom January 2009 to April 2012, we received 467 AFB smear-positive sputum specimens. A total of 95 CT scans obtained from the 159 patients were analyzed, 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 17 publications
2
22
0
3
Order By: Relevance
“…One adult with chronic Mycobacterium abscessus infection scheduled for elective surgery at the NIH Clinical Centre gave written consent to participate under NIAID study “Study of Mycobacterial Infections” ( www.ClinicalTrials.gov#NCT00018044 ). This participant had pulmonary nontuberculous mycobacterial disease presenting with cavitary lesions, well-organized necrotizing granulomas, and non-necrotizing granulomas similar to those described previously in lung disease caused by non-TB mycobacteria and M. tuberculosis 33 35 . This 73 year-old female participant was administered 600mg RIF and 100mg CFZ daily among other anti-mycobacterial medications as part of her standard drug regimen (24h target group, 26h (for RIF) and 27h (for CFZ) actual times of vessel ligation post drug administration).…”
Section: Methodssupporting
confidence: 60%
“…One adult with chronic Mycobacterium abscessus infection scheduled for elective surgery at the NIH Clinical Centre gave written consent to participate under NIAID study “Study of Mycobacterial Infections” ( www.ClinicalTrials.gov#NCT00018044 ). This participant had pulmonary nontuberculous mycobacterial disease presenting with cavitary lesions, well-organized necrotizing granulomas, and non-necrotizing granulomas similar to those described previously in lung disease caused by non-TB mycobacteria and M. tuberculosis 33 35 . This 73 year-old female participant was administered 600mg RIF and 100mg CFZ daily among other anti-mycobacterial medications as part of her standard drug regimen (24h target group, 26h (for RIF) and 27h (for CFZ) actual times of vessel ligation post drug administration).…”
Section: Methodssupporting
confidence: 60%
“…However, other CT findings to distinguish the significance between NTM and PTB are rarely reported. Yuan et al 20 compared chest CT findings in 75 PTB and 20 NTM-LD patients and found that bronchiectasis, pleural effusion, and pulmonary nodules could be used to distinguish PTB from NTM with statistically significance. Conversely, we found that the type of cavity and the nodule's size were not classified and sample size was relatively smaller in term of atelectasis, mediastinal lymph node enlargement and calcification, which may have caused a certain deviation while performing data analysis.…”
Section: Number Of Patients Involvedmentioning
confidence: 99%
“…HRCT scanning allows early detection and better differentiation between colonization and invasive infection that are not visible on the chest X-ray [97]. In CT features; pleural effusion and nodules are significantly more common in patients with pulmonary TB (PTB) while bronchiectasis combined with cystic changes are significantly more common in patients with NTM lung infections [98]. Bronchiectasis in the right middle lobe or left lingual segment and thin-walled cavity with a diameter of more than 3 cm are the frequent chest CT features in patients with NTM-LD [99].…”
Section: Clinical and Radiographic Based Diagnosismentioning
confidence: 99%
“…Also, NTM lung infection can present itself with different radiological patterns, while two main patterns, fibrocavitary form and nodular bronchiectatic form, have been observed frequently [100]. The fibrocavitary form is usually characterized by upper lobe cavities with areas of increased opacity and with or without calcification (Figure 2) [98,101].…”
Section: Clinical and Radiographic Based Diagnosismentioning
confidence: 99%